Crescimento e acúmulo de nutrientes das pitaias vermelha e saborosa - Lima, Denise de Castro (2018)
Knowledge in regard to quantities of accumulated nutrients during development stages of the pitaya is extremely important since it makes possible to determine the periods in which essential elements are mostly required, thus contributing to the elaboration of rational fertilization programs for the crop, reducing production costs. In the view of the above, the present research aimed to evaluate the growth and the nutritional demand of two species of pitaya, estimate accumulation of macro and micronutrients by the plants, and determine the epochs in occur the highest accumulations of dry matter mass and nutrient exports. Two different experiments were conducted, in which one has used red pitaya (Hylocereus sp.), and the other one used pitaya tasty (Selenicereus setaceus Rizz.) as test plant. Both experiments lasted one year and were performed at the Agriculture Sector of the Department of Crop Science at the Center of Agricultural Science of Federal University of Ceará. Pitaya seedlings were planted in pots filled with Eutrophic Red-Yellow Argisol and taken to an outside field. The designs used in both experiments were randomized blocks with four repetitions and seven periods of sampling: 0, 60, 120, 180, 240, 300 and 360 DAP (days after planting). It was assessed, for each period of sampling, the length of cladodes, mass of dry matter of aerial part, number of flower buds, flowers and fruits, and the accumulation of nutrients in the aerial part. The red pitaya has presented continuous growth and fruit production starting from 240 days after planting. Nutrients accumulation has occurred in descending order as the following: K > Ca > N > P > Mg > S > (Na element) > Zn > Mn > Fe > B > Cu. Potassium and nitrogen were the macronutrients most exported by the fruits, and zinc and boron were the most exported among micronutrients. Pitaya tasty has presented continuous growth during the 360 days. Nutrients accumulation has occurred in descending order as the following: K > Ca > N > P > Mg > S > (Na element) > Zn > Fe > Mn > B > Cu. Pitaya tasty has not showed production during the one year experimental period.